Media Promosi E-Catalogue di Instagram pada Indio Makeup Singosari Malang - Fania Ardani; Dwi Sudjanarti (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Indio Makeup Artist is an SME specializing in makeup services. The word-of-mouth promotion used by Indio Makeup Artist is considered less effective in attracting potential customers. Therefore, creating an e-catalogue to be published on Instagram is necessary. This research aims to develop an innovative e-catalogue promotion for Indio Makeup Artist. This research uses the action research method, which involves distributing questionnaires to the owner, 2 design experts, 2 marketing experts, and 10 potential customers. The marketing experts' questionnaires are assessed using the EPIC method (Empathy, Persuasion, Impact, and Communication). Meanwhile, the questionnaires for design experts and the owner use criteria for evaluating a good e-catalogue design (Theme, Writing and Language, and Product Photos). The results of the research indicate that the e-catalogue design is categorized as very good. The design score received a rating of 4.6, which falls into the excellent category. The EPIC score also received a rating of 4.6, classifying it as highly effective. It can be concluded that the e-catalogue is suitable for publishing to help promote Indio Makeup Artist. The recommendation is that the e-catalogue should be promoted through Instagram Stories using the available link.